1988
DOI: 10.1002/ar.1092200213
|View full text |Cite
|
Sign up to set email alerts
|

Innervation of muscle receptors in the cross‐reinnervated soleus muscle of the cat

Abstract: It has recently been reported (Gregory et al., J. Physiol., 331:367-383, 1982) that cutting a muscle nerve and letting it grow back into the muscle or cross-uniting the muscle with a foreign nerve results in major disruption of the normal response patterns of muscle spindles and tendon organs. Here we report observations on the structure of muscle receptors in cross-reinnervated and self-reinnervated soleus muscles in an attempt to detect abnormalities that might account for their disturbed function. Eight sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…2C). These features of muscle spindles reinnervated after nerve section are documented in several previous reports (Banks et al, 1985;Ip et al, 1988;Banks and Barker, 1989;Dieler and Schroder, 1990;Dieler et al, 1992;Barker et al, 1993). Banks and Barker (1989) give evidence that regenerated annulospiral endings in the equatorial region of intrafusal fibers are likely produced by regenerated group Ia afferents, although reinnervation by other proprioceptive afferents, i.e., groups Ib and II, cannot be ruled out.…”
Section: Recovery Of Proprioceptive Afferents/receptorssupporting
confidence: 74%
See 1 more Smart Citation
“…2C). These features of muscle spindles reinnervated after nerve section are documented in several previous reports (Banks et al, 1985;Ip et al, 1988;Banks and Barker, 1989;Dieler and Schroder, 1990;Dieler et al, 1992;Barker et al, 1993). Banks and Barker (1989) give evidence that regenerated annulospiral endings in the equatorial region of intrafusal fibers are likely produced by regenerated group Ia afferents, although reinnervation by other proprioceptive afferents, i.e., groups Ib and II, cannot be ruled out.…”
Section: Recovery Of Proprioceptive Afferents/receptorssupporting
confidence: 74%
“…2 A), and, in normal animals, these endings are generated by group Ia afferents (Barker, 1974). In the contralateral MG muscles that were self-reinnervated after nerve cut, we found that most muscle spindles (Ͼ75%) ( Table 1) received a nerve supply (Banks et al, 1985;Ip et al, 1988). More than half of these spindles exhibited regular transverse bands of annulospiral endings in the equatorial region of intrafusal fibers similar to normal spindles (Table 1; Fig.…”
Section: Recovery Of Proprioceptive Afferents/receptorsmentioning
confidence: 71%
“…In the tenuissimus experiments 43 % of spindles (n = 58) were reinnervated by I a afferents as compared with 21 % of peroneus brevis spindles after complete section of the common peroneal nerve ( Table 2). In the histological analysis by Ip, Luff & Proske (1988) of the soleus muscles that were selfor cross-reinnervated in the experiments by Gregory et al (1982) only 3% of spindles were observed to have regenerated annulospiral primary endings (presumably Ia) among 180 examined. This may reflect the fact that in these experiments the nerve stumps were simply tied together with silk thread without attempting epineurial repair or fascicular alignment.…”
Section: Process and Quality Of Recoverymentioning
confidence: 95%
“…In addition, several studies showed return of the reflex response, with one study demonstrating restoration of up to 70% of normal reflex contraction tension in rats 21,23,49 . A possible explanation for incomplete sensory recovery in muscle is abnormal reinnervation and ultrastructural changes in a fraction of the sensory end organs and nerve endings 19,20,25,26,31,40 . This may explain why some studies have demonstrated abnormal neural response and/or reflex muscle contraction despite evidence of successful regeneration and reinnervation 53,54 .…”
Section: Methodsmentioning
confidence: 99%